PENALARAN DALAM TULISAN EKSPOSITIF SISWA KELAS X SMK NEGERI 5 KABUPATEN TEBO - Mufidah Umaroh; Akhyaruddin ,; Agus Setyonegoro (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2016)
Abstact The purpose of this studi is to describe reasoning in the expositive writings of students of class X SMK Negeri 5 Kabupaten Tebo based on the types of reasoning, namely: (1) inductive reasoning and (2) deductive reasoning. This research uses quantitative descriptive method. The population of this study are the students of class X SMK Negeri 5 Kabupaten Tebo consisting of 4 classes with 104 students. The sampling technique was randomized using a random proportional sampling method. The sample used is 25% of 104 students is 26 students. The results show that reasoning in expositive writing is considered good quality criterion. This is evident from both reasoning elements: (1) the reasoning of induction includes: (1) generalized induced reasoning in expository paragraphs, (2) reasoning of inductions by analogy in expository paragraph, (3) (2) deductive reasoning in the expository paragraph, and (2) the deductive reasoning in entiphat in the expository paragraph turns out the student's average score of 80.48%. Keywords: reasoning, exposure